Paratexts in Translation Nordic Perspectives - Pleijel, Richard; Podlevskikh Carlström, Malin (Frank & Timme, 2022)
As something that surrounds, extends, and presents a text to the world, the phenomenon of paratext is gaining more and more attention within the discipline of Translation Studies. This edited volume, with contributions by five Nordic scholars, aims to build on that attention by presenting five case studies on paratexts in translations into Danish, Norwegian, and Swedish. A special focus lies on the paratextual mechanisms at play when works from different source cultures are translated into a Nordic target context. The translated works under scrutiny belong to genres such as literary novels, non-fiction works, and religious texts, and the paratexts surveyed include footnotes, covers, blurbs, introductions, and literary reviews. The scholars represented in the volume all work in Translation Studies, or at the intersection between Translation Studies and other disciplines.